Carbon-Based Electric Double-Layer Supercapacitors For Pulse Power Applications - Ramasamy, Vimala (2005)
Electric double-layer capacitors(EDLC) also known as supercapacitors, represent a very promising alternative batteries, eapecially in pulse power applications. The study is initiated to integrate the carbon nanotechnology advances into supercapacitors. Nanosized-electrode-material provides higher surface area.